PENETAPAN PARAMETER SPESIFIK DAN NON SPESIFIK EKSTRAK KULIT SEMANGKA - Zulfa Nur Fadhila; Aprilia Ayu Dewayanti; Dear Syairi; Odilia Putri Daniati; Tarisa Silvi Nugraheni; Disa Andriani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
k, and yellow) while the rind is underutilized by the community. The purpose of the study is to prove that watermelon extract has chemical properties such as flavonoid and others, determining the parameters for the extract of the watermelon rind by established standards and proving the antioxidant compounds in the watermelon's rind. Watermelon extract is obtained by way of an extraction of the maceration method using ethanol 70%, resulting in a yield of 10,32%. Oilshaped extract with a distinctive odor and alkaloids, steroids, and flavonoids. The essence of ethanol soluble watermelon rind extract is 40%, whereas the water content is 60%. Distilled extract by 8,070%. The ash count was 19,5%. Based on the results of the study, it could be concluded that specific parameters (Identification, organoleptis, chemical testing, ethanol-soluble extract, and watersoluble extract) and non-specific parameters (determination of drying losses and the total ash content) on the watermelon rind extract meet the establishedstandards.